2018
DOI: 10.1177/0886260518780783
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Venue Characteristics Associated With the Practice of Physical and Sexual Aggression in Brazilian Nightclubs

Abstract: Violence among young adults is an increasing public health concern, especially in the context of nightlife, such as around nightclubs and bars. Nightlife is associated with alcohol, drugs, and increased violence, but little is known about personal and environmental factors related to physical aggression and sexual violence in nightclubs. This study aimed to determine personal and environmental risk factors for physical and sexual aggression in nightclubs in São Paulo, Brazil. Data were collected among nightclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…Across these studies, prevalence of sexual violence victimisation experienced on the night of survey ranged from 10% (kissed or tried to have intercourse against will, in nightclubs in Brazil; Santos et al, 2015) to 50% (unwanted and/or persistent sexual aggression, on night out in Canada; Graham et al, 2014a). Reported prevalence of sexual violence perpetration was less than one in twenty (across two studies of the same population: Fung et al, 2018;Santos et al, 2015).…”
Section: Nature and Extent Of Nightlife-related Sexual Violencementioning
confidence: 99%
See 4 more Smart Citations
“…Across these studies, prevalence of sexual violence victimisation experienced on the night of survey ranged from 10% (kissed or tried to have intercourse against will, in nightclubs in Brazil; Santos et al, 2015) to 50% (unwanted and/or persistent sexual aggression, on night out in Canada; Graham et al, 2014a). Reported prevalence of sexual violence perpetration was less than one in twenty (across two studies of the same population: Fung et al, 2018;Santos et al, 2015).…”
Section: Nature and Extent Of Nightlife-related Sexual Violencementioning
confidence: 99%
“…Six studies identified relationships between socio-demographics (i.e. age, gender and ethnicity) and sexual violence (Fung et al, 2018;Hughes et al, 2008;Miller et al, 2015;Parks and Zetas-Zanatta, 1999;Sanchez et al, 2019;Thompson and Cracco, 2008). Some studies suggested that females were more likely than males to experience nightlife-related sexual violence as a victim, and males more likely to be a perpetrator (Fung et al, 2018;Hughes et al, 2008).…”
Section: Individual Levelmentioning
confidence: 99%
See 3 more Smart Citations